Flower trade‐wind clouds are shallow mesoscale convective systems. (19th December 2022) - Dauhut, Thibaut; Couvreux, Fleur; Bouniol, Dominique; Beucher, Florent; Volkmer, Lea; Pörtge, Veronika; Schäfer, Michael; Ayet, Alex; Brilouet, Pierre‐Etienne; Jacob, Marek; Wirth, Martin
Abstract: Flower clouds are trade‐wind shallow cumuli, with tops reaching 3 km altitude, organised into 100‐km wide clusters. They are widespread over the subtropics and associated with the strongest cloud radiative effect among trade‐wind cumuli mesoscale organisations. In the context of large uncertainty in climate projections due to the representation of shallow clouds, major knowledge gaps remain about the global impact of mesoscale organisations and the local processes driving them. Here, the processes governing the flower organisation are investigated based on the case study of February 2, 2020 from the Elucidate the Couplings Between Clouds, Convection, and Circulation (EUREC 4 $$ {}^4 $$ A) campaign, east of Barbados. One flower cloud is simulated with a large‐eddy simulation (LES), using the Meso‐NH model at 100‐m horizontal grid spacing, and validated extensively with high‐resolution observations from the High Altitude and Long‐range Research Aircraft (HALO), dropsondes, and satellite measurements. The cloud‐top altitudes exhibit a trimodal distribution. The processes shaping flower clouds are wide cold pools and cloudy updrafts organised in one large arc at the western edge. These updrafts are responsible for the highest cloud tops and drive most of the vertical turbulent fluxes of sensible heat, humidity, and momentum. A mesoscale circulation takes place at the scale of the flower clouds and makes them very similar to deep mesoscale convective systems. Abstract : Flower clouds are trade‐wind shallow cumuli organised into 100‐km wide clusters. The processes driving their organisation are investigated using a large‐eddy simulation (100‐m horizontal grid spacing), which is validated extensively with high‐resolution observations from the EUREC 4 $$ {}^4 $$ A field campaign. The key processes are wide cold pools and cloudy updrafts organised in one large arc at the western edge of the cloud. A mesoscale circulation takes place at the scale of the flower clouds and makes them very similar to deep mesoscale convective systems.